How Does Leader Humility Influence Team Creativity? The Roles of Team Behavioral Integration and Leader Performance - Zhu, Taiqiu; Chen, Yixuan; Asante, Eric Adom; Zhu, Yue; Xu, Tingting (Frontiers in Psychology, 2022)
This study developed and tested a research model to examine the influence of leader humility on team creativity. Drawing on social learning theory, we tested team behavioral integration as a mediator in the relationship between leader humility and team creativity. Moreover, we tested the moderating effect of leader performance on this mediated relationship. We tested our hypotheses using a multiple-source research design. Data were collected from 275 employees in 67 work teams from a variety of industrial companies in Southeast China. The results confirmed that team behavioral integration mediated the relationship between leader humility and team creativity. Furthermore, the indirect effect of leader humility on team creativity via team behavioral integration was stronger when leader performance was higher (vs. lower). We discuss the implications of our findings for the theory and practice of leader humility.